Insegnanti, stereotipi di genere e pratiche educative inclusive Progetto PARIS, la PArità impaRIamola a Scuola - Cabras, Cristina (RESOCONTI, 2022)
The research, conducted on a sample of 822 preschool, primary and secondary school teachers in the Sardinian regional territory, aims to investigate risk factors (resistance to change, sexism, traditionalist attitude in parenting) and protective factors (perceived self-efficacy, social and moral norms regarding gender equality, positive attitude toward gender diversity) in the adoption of inclusive teaching practices. Standardized self-report survey instruments are used, administered via an online platform during March-May 2022. Relationships between variables were investigated by bivariate correlation analysis, linear regression and mediation models. The results allow for evidence of a significant relationship between self-efficacy, teachers' moral norms, and adoption of inclusive educational practices, but these relationships are negatively mediated by resistance to change (fear and stress in the affective component, protests and objections against change toward equality).